Taxonomic delimitation in color polymorphic species of the South American grasshopper genus Diponthus Stål (Orthoptera, Romaleidae, Romaleini) - Pocco, Martina Eugenia (2014)
The South American genus Diponthus Stål comprises species with cryptic and probably aposematic colorations. It belongs to a group of grasshoppers, tribe Romaleini, where color polymorphism is common. Morphometric techniques were used to clarify the taxonomic limits and status of six nominal species of Diponthus: D. permistus (Serville), D. argentinus Pictet & Saussure, D. pycnostictus Pictet & Saussure, D. communis Bruner, D. pictus (Bolivar) and D. schulzi Bruner. Results of cluster (CA) and principal component (PCA) analyses showed that D. pycnostictus can be defined by a unique combination of characters, while the remaining nominal species represent different color morphs of a single taxon, here recognized as D. argentinus. We also used statistical analyses to examine whether the discontinuities in body coloration of the polymorphic D. argentinus could be explained by geographic variation. The distribution patterns of body coloration of D. argentinus do not appear to be restricted to any particular biogeographic region and no character correlation resulted with latitude. Furthermore, the results show that color morphs display high levels of overlap across the geographic range, as well as intra-population variation. We conclude that in D. argentinus body coloration varies considerably across the geographic distribution range but without any noticeable color gradient correlated with the latitude. According to the phylogenetic species concept (PSC) we consider D. pycnostictus Pictet & Saussure and D. argentinus Pictet & Saussure as valid species. The following synonymies are proposed under D. argentinus: D. communis Bruner n. syn., D. schulzi Bruner n. syn., D. pictus (Bolivar) n. syn., and D. permistus (Serville) n. syn. We declare D. permistus (Serville) a nomen oblitum.